SISTEM PENILAIAN KINERJA PENGAJAR MENGGUNAKAN METODE AHP DAN TSUKAMOTO (STUDI KASUS : LEMBAGA BAHASA DAN ILMU AL QUR’AN) - Rizal, Muhamad; Hardiansyah, Alim; Kusmawan, Oki (ISTEK WIDURI, 2023)
LBIQ is one of the non-regional apparatus institutions in the field of religion which organizes education and teaching of Arabic and Al-Qur'an Studies in the Special Capital Region of Jakarta Province. LBIQ carries out teacher performance evaluations by giving questionnaires to students. Assessment competency criteria for LBIQ Teachers include Discipline competence, Pedagogic competence and Attendance competence. The main objective of the teacher's performance assessment is to find out the level of teacher performance, with the results of the evaluation it is hoped that it can become material for improving teacher performance so that the quality of the teaching system within the Institute for Arabic Language and Al-Qur'an Studies can improve in order to create positive things about performance Teachers in carrying out their work, especially in the teaching and learning process. The aim of the research is to design a decision support system for evaluating teacher performance using the AHP and Tsukamoto methods in order to provide teacher performance assessment results that are in accordance with the selected criteria. Application of the AHP and Tsukamoto methods in assessing the results of teacher performance evaluation at LBIQ Jakarta in the form of a web-based application using the PHP programming language. The implementation of the system created can input teacher performance data as well as input questionnaire data and make it easier for system users to make assessments so they can determine the best teacher. Business. From the results of testing the Analythical Hierarchy Process (AHP) and Tsukamoto Methods, the AHP method is more accurate in assessing the performance of teachers at LBIQ with the final result being a rating/rank compared to the Tsukamoto method, while the Tsukamoto method is more effective in assessing the performance of this teacher with the final result in the form of value.